Evaluación del nivel de calidad de las empresas de servicio que impactan en el sector turístico de Cartagena de Indias (2009)
The aim of this paper is to do a study of quality level measuring offered by different companies which interact in the tourism segment of the city of Cartagena de Indias in sectors as: Restaurants, clothing stores, Clubs and Cafe Internet, as a step to know the level of customer satisfaction and thus, determinate possible actions for improvement in the delivery of its services. Therefore, it’s proposed that these companies use in their service’s measuring the SERVQUAL model, enabling them first, identify which areas are failing; second, know what their customers need, which is what they really want, and third, what are the steps to be followed to achieve satisfied and loyal costumers. For this investigation the mechanism most used for data collection was the survey, it where made 3 different types to each sectors. These were made to managers, employees and last, for customers. Then, with this information we proceeded to analyze the results and draw conclusions about the service quality that each company was providing. In this way, it was achieved the stated objective.